Social norms or low-cost heuristics? An experimental investigation of imitative behavior - Simona Cicognani; Luigi Mittone (Kiel Institute for the World Economy (IfW), 2014)
This paper extends choice theory by allowing for the interaction between cognitive costs and social norms. The authors experimentally investigate the role of imitation and temporal decisional patterns when participants face a task which is costly in cognitive terms. They identify two main reasons for imitative behavior. First, individuals belonging to a community might want to conform to others to obey to social norms. Second, individuals might be boundedly rational and consider imitation as a decisional device when comparing alternatives is cognitively demanding. In order to empirically disentangle the two effects, the authors present a laboratory experiment in which they model the choice of different alternatives through high or low cognitive costs and feedback information given to subjects. Their results do not provide strong evidence for imitative behavior. They find instead a temporal pattern in the distribution of choices, both in the high-cost and low-cost conditions.
Keywords: C92; D81; Z13; 330; social norms; cognitive costs; laboratory experiments